Pengaruh Sosialisasisi Perpajakan dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak Orang Pribadi di KPP Pratama Metro - Agung Laksono; Syamsu Rizal (Institut Bisnis dan Informatika Kesatuan, 2022)
Taxes are one of the important instruments in state revenues in the state budget as well as routine and non-routine expenditures of a country that will support national development. The addition of the number of taxpayers every year always increases, but the increase is not in accordance with compliance in paying taxes. This is an obstacle in achieving and maximizing tax revenue. The purpose of this study was to determine the effect of taxation socialization and tax sanctions on individual taxpayer compliance at the Pratama Metro Tax Service Office. The population in this study were individual taxpayers registered at the Pratama Metro Tax Office, amounting to 91,967 people and the sample used in this study was 100 respondents who were generated by calculations using the Slovin formula. Determination of the sample using non-probability sampling method with purposive sampling technique. The data collection method used field research with questionnaires measured by a Likert scale. Analysis of the data using multiple linear regression analysis and hypothesis testing. The results of this study indicate that taxation socialization and tax sanctions have a significant effect on individual taxpayer compliance at the Pratama Metro Tax Service Office.